Partnerships for involving small-scale growers in commercial forestry: lessons from Australia and Indonesia - Race, D.; Bisjoe, A.R.; Hakim, M.R.; Hayati, N.; Julmansyah; Kadir, A; Kurniawan; Kusumedi, P.; Nawir, A.A.; Nurhaedah; Perbatasari, D.U.; Purwanti, R.; et al. (2009)
The trade relationship between small-scale growers and processing companies often plays an important role in determining the nature and extent of benefi ts derived from commercial forestry, and the distribution of these benefi ts. Many strategies are used by individual small-scale growers, village communities, companies and government agencies to form partnerships to undertake commercial forestry – including outgrower schemes, land leasing by companies, and using intermediary brokers between small-scale growers and processors. This article reports on the key fi ndings of a three-year research project that explored different business partnerships used in commercial forestry in Australia and Indonesia, and identifi ed the critical factors for benefi cial and enduring partnerships. The key lessons from this research are that, for many small-scale growers to form successful partnerships with other investors, they need: increased knowledge of the operations and components of commercial forestry; improved access to competitive markets; increased knowledge of the dynamics of forest product markets; improved capacity of local farmer forest groups to share experiences and information, and build their knowledge of commercial forestry; and reduced administrative and fi nancial burden imposed by government on small-scale forestry operations